2017
DOI: 10.1007/s11033-017-4122-3
|View full text |Cite
|
Sign up to set email alerts
|

Dishevelled proteins and CYLD reciprocally regulate each other in CML cell lines

Abstract: Dishevelled (Dvl) proteins are activated by Wnt pathway stimulation and have crucial roles in the regulation of β-catenin destruction complex. CYLD is a tumor suppressor and a deubiquitination enzyme. CYLD negatively regulates the Wnt/β-catenin signaling pathway by deubiquitinating Dvl proteins. Loss of function and mutations of CYLD were linked to different types of solid tumors. Loss of function in CYLD is associated with Dvl hyper ubiquitination, resulting in the transmission of Wnt signaling to downstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In agreement, A20 prevents inflammatory reactions in psoriatic arthritis-like disease [29], and the inactivation of A20 is related to psoriasis severity [18]. Unlike A20, the inactivation of CYLD is found in blood cancers, including leukemia [13], and a downregulated expression of Cezanne is reported in solid cancers, such as hepatocellular carcinoma [16].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In agreement, A20 prevents inflammatory reactions in psoriatic arthritis-like disease [29], and the inactivation of A20 is related to psoriasis severity [18]. Unlike A20, the inactivation of CYLD is found in blood cancers, including leukemia [13], and a downregulated expression of Cezanne is reported in solid cancers, such as hepatocellular carcinoma [16].…”
Section: Discussionmentioning
confidence: 67%
“…Among them, deubiquitinase (DUB) genes, including tumor necrosis factor α-induced protein 3 (TNFAIP3, A20), tumor suppressor cylindromatosis (CYLD) and Cezanne, play important roles in deubiquitinating target proteins by cleaving their polyubiquitin chains to suppress the activation of downstream signalling pathways. The attenuated expression of A20 and CYLD is shown in patients with leukemia/lymphoma [13][14][15] and Cezanne is down-regulated in hepatocellular carcinoma [16]. A20 variants are associated with susceptibility to psoriasis in a Japanese population [17].…”
Section: Introductionmentioning
confidence: 99%
“…Cyld negatively regulates NF-kB, known to be one of the most important players in inflammation and liver cancer [57], and the MAPK signaling cascade [58,59] by removing ubiquitin chains from signaling molecules, such as NEMO, TRAF2, TRAF6, TRAF7, TAK1 and RIP1 [60]. Moreover, Cyld induces the decrease in Wnt/β-catenin signaling activity by disheveled deubiquitination [61] and is considered an important regulator of necroptosis [62]. Furthermore, Nikolau et al [63] demonstrated that Cyld is involved in the regulation of hepatocyte homeostasis and that its inactivation causes inflammation, fibrosis and cancer through chronic activation of the TGF-beta-activated kinase (TAK1) and c-Jun N-terminal kinase (JNK).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these substrates act as CSCs factors, which can activate and upregulate the SRSs. For example, the upregulation of CYLD causes DVL deubiquitination, significantly inhibiting the oncogenic Wnt pathway, thereby inhibiting the occurrence of tumors ( Caliskan et al, 2017 ). The downregulation of CYLD promotes the accumulation of β-catenin in the nucleus through ubiquitination of DVL at Lys-63 ( Tauriello et al, 2010 ).…”
Section: Dubs Involved In Stem Cell Factors Srss and Itaimmentioning
confidence: 99%